1984
DOI: 10.1016/s0006-3495(84)84269-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the orientational ordering of carotenoids in lipid bilayers by resonance-Raman spectroscopy

Abstract: The orientational ordering of beta-carotene and crocetin embedded in lamellar model membranes has been investigated by angle-resolved resonance Raman scattering at a temperature well above the phase transition of the lipid chains. It is shown that the ordering of the carotenoids is dependent on the chemical composition of the lipid bilayers. The orientational distribution functions found clearly show that beta-carotene is oriented parallel to the bilayer plane (dioleoyl lecithin) or perpendicular to it (soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…It has been reported that the length of the dihydroxycarotenoid molecules (the distance between hydroxyl groups is 30.2 Å) is matched to the thickness of the hydrocarbon interior of the phosphatidylcholine bilayer, and it is assumed that lutein and zeaxanthin adopt an orientation mainly perpendicular to the membrane surface (33). Van de Ven et al (34) indicated that the orientation of ␤-carotene is parallel to the membrane surface in the dioleoylphosphatidylcholine bilayer, perpendicular to the membrane surface in a soybean-phosphatidylcholine bilayer, and both parallel and perpendicular in dimyristoylphosphatidylcholine membranes (34). It was also reported that the localization of macular xanthophylls, such as zeaxanthin and lutein, in detergent-soluble membranes was about six times more abundant than in the detergent-resistant membranes considered as lipid rafts (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the length of the dihydroxycarotenoid molecules (the distance between hydroxyl groups is 30.2 Å) is matched to the thickness of the hydrocarbon interior of the phosphatidylcholine bilayer, and it is assumed that lutein and zeaxanthin adopt an orientation mainly perpendicular to the membrane surface (33). Van de Ven et al (34) indicated that the orientation of ␤-carotene is parallel to the membrane surface in the dioleoylphosphatidylcholine bilayer, perpendicular to the membrane surface in a soybean-phosphatidylcholine bilayer, and both parallel and perpendicular in dimyristoylphosphatidylcholine membranes (34). It was also reported that the localization of macular xanthophylls, such as zeaxanthin and lutein, in detergent-soluble membranes was about six times more abundant than in the detergent-resistant membranes considered as lipid rafts (35).…”
Section: Discussionmentioning
confidence: 99%
“…Orientation of polar and nonpolar carotenoids (including their cis -forms) in the lipid-bilayer membrane has been investigated by many laboratories [19,44,47,58,59]. It is suggested that the presence of polar hydroxyl groups at the ends of carotenoid molecules and their transmembrane orientation (as in the case of zeaxanthin and lutein) enhance their antioxidant properties , as compared with the antioxidant properties of monopolar (β-cryptoxanthin) and nonpolar (β-carotene) carotenoids [40,60].…”
Section: Antioxidant Potency Of Macular Xanthophylls In Membranesmentioning
confidence: 99%
“…The length of a typical carotenoid matches the thickness of the hydrophobic membrane core (6). The molecular architecture of these pigments is responsible for their localization and orientation in the membranes and for their effects on the membrane properties (7)(8)(9)(10). Studies on a mixture of liposomes and carotenoids demonstrated that formation of the hydroxy derivatives of these compounds not only increased the rigidity of the lipid phase, but also blocked the penetration of protons through the membrane (11) and significantly decreased the oxygen diffusionconcentration product in the hydrocarbon region of model membranes (12).…”
mentioning
confidence: 99%